Pengaruh Tehnik Counterpressure Terhadap Pengurangan Rasa Nyeri Pada Persalinan Ibu Bersalin Kala I Di Klinik Bidan Nyanyas Tahun 2024 - Metha Solihati Rayuna; Fitriana Sari; Tenang Juvita Sitepu (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2025)
Labor is the process of opening and thinning the cervix, as well as uterine contractions, and the fetus descends into the birth canal, causing pain in labor. One of the efforts to reduce labor pain is the counterpressure technique. This study aims to determine the effect of counterpressure techniques to reduce labor pain in first-time laboring mothers at the Nyanyas Midwife Clinic, Arcamanik City, Bandung, 2024. This study used a quasy experiment (pseudo experiment) with a Two-Group Pre-Postest design. The sampling method in this study used total sampling of active phase I laboring mothers. The results showed that the counterpressure technique was more effective for reducing pain levels in active phase laboring women.